Likuiditas Obligasi di Tengah Asimetri Informasi dan Inflasi pada Manufaktur BEI 2023-2025 - Nikke Yusnita Mahardini; Santi Octaviani; Yuni Pristiwati Noer Widianingsih (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2026)
This study examines factors affecting corporate bond liquidity in manufacturing firms listed on the Indonesia Stock Exchange during 2023–2025. The variables include bond maturity, bond size, bond capitalization, bond rating, bid-ask spread, and inflation. A quantitative approach is used with secondary data from the Indonesia Stock Exchange, PEFINDO, company financial reports, and the Central Bureau of Statistics. The sample consists of 129 bond observations selected through purposive sampling and analyzed using multiple linear regression. The results show that bond maturity, bid-ask spread, and inflation significantly and negatively affect bond liquidity. In contrast, bond size and bond rating have a significant positive effect, while bond capitalization is not significant. These findings indicate that information quality, transaction costs, and macroeconomic conditions play key roles in determining corporate bond liquidity. The study provides implications for investors, issuers, and regulators in improving the efficiency of the corporate bond market.